1992
DOI: 10.1002/bip.360320809
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies of anionic melittin analogues: Effect of peptide concentration, pH, ionic strength, and temperature—models for protein folding and halophilic proteins

Abstract: Melittin (MLT), a 26-residue cationic (net charge +5 at pH 7.2) peptide from bee venom, is well known to be a monomeric, approximately random coil; but when its charges are reduced by titration, by acetylation (net charge +2) or succinylation (net charge -2), or by screening by salt, it goes over to tetrameric alpha-helix. The conversion is promoted by raising the peptide concentration. The tetramer is held together by hydrophobic forces. We have changed the net charge to -6 by acylation with acetylcitric anhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…The dramatic effects of pH and salt on protein folding observed in this study and previously in model coiled-coils (Zhou et al, 1994b) and other model helical proteins (Ramalingam et al, 1992) have suggested major implications for the potential of de novo design of environmentally sensitive proteins. One of the best examples of salt effects on protein folding in native proteins is the case of extreme halophilic bacteria, which are adapted to living in high salt concentration environments and whose cytoplasm is close to saturated in KCl.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The dramatic effects of pH and salt on protein folding observed in this study and previously in model coiled-coils (Zhou et al, 1994b) and other model helical proteins (Ramalingam et al, 1992) have suggested major implications for the potential of de novo design of environmentally sensitive proteins. One of the best examples of salt effects on protein folding in native proteins is the case of extreme halophilic bacteria, which are adapted to living in high salt concentration environments and whose cytoplasm is close to saturated in KCl.…”
supporting
confidence: 59%
“…This stabilization may be due to the combined effects of the salt stabilizing the hydrophobic core as well as interactions of hydrated salt ions with the surface of the folded protein (Zaccai and Eisenberg, 1990). It has been suggested that clustering of negatively charged residues on the surface of halophilic proteins may cause structural instability, possibly due to charge repulsion, that is removed by the effects of salts (Ramalingam, et al, 1992). pH sensitivity of coiled-coil formation has recently been illustrated for the influenza virus hemagglutinin protein, which is required for fusion of the viral and cellular membranes.…”
mentioning
confidence: 99%
“…Monomeric melittin having the trans and cis proline, if it is necessary to make a clear distinction, will be referred to as the trans-and cis-monomer, respectively. By variation in pH or salt concentration or temperature of an aqueous solution, a conformation transition between the tetramer and the monomer is induced (Bello et al 1982;Faucon et al 1979;Goto and Hagihara 1992;Hagihara et al 1992Hagihara et al , 1994Iwadate et al 1998;Miura 2011;Quay and Condie 1983;Ramalingam et al 1991Ramalingam et al , 1992Wilcox and Eisenberg 1992). Interestingly, melittin undergoes the transition not only by heating but also by cooling from room temperature like a globular protein such as myoglobin or staphylococcal nuclease (Privalov 1990).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, BN28 may exist in a helical conformation in vivo given the proper cellular environment. High ionic concentrations can stabilize helices in peptides that are unstructured in low-ionicstrength environments (Ramalingam et al, 1992). It is believed that this stabilization is accomplished through either charge screening or enhancement of weak hydrophobic interactions.…”
Section: Dlscusslonmentioning
confidence: 99%